Inhalation and oral toxicokinetics of 6:2 FTOH and its metabolites in mammals. (February 2015) - Russell, Mark H.; Himmelstein, Matthew W.; Buck, Robert C.
Highlights: Toxicokinetics of 6:2 FTOH and metabolites evaluated in rats and humans. Single and repeated dose exposure studied in rats via inhalation and oral gavage. Yields and elimination half-lives determined for PFBA, PFHxA, PFHpA and 5:3 Acid. Elimination half-lives of PFHxA, PFHpA and 5:3 Acid determined in humans. Abstract: The toxicokinetics of 6:2 fluorotelomer alcohol (6:2 FTOH) and its terminal perfluorinated and polyfluorinated metabolites (PFBA, PFHxA, PFHpA and 5:3 Acid) have been calculated from laboratory studies of rats and from a biomonitoring study of humans. In vitro studies with mouse, rat and human hepatocytes indicate qualitatively similar metabolic pathways of 6:2 FTOH. In a one-day inhalation study of 6:2 FTOH in rats, PFBA, PFHxA, PFHpA and 5:3 Acid were determined to be the major metabolites in plasma with calculated elimination half-lives of 1.3–15.4 h and metabolic yields up to 2.7 mol%. In five-day and 23-day inhalation studies and a 90-day oral study of 6:2 FTOH, the plasma or serum concentration profile of 5:3 Acid was several-fold higher than concentrations observed in the single day study, resulting in an estimated elimination half-life of 20–30 d. In contrast, the concentrations of PFBA, PFHxA and PFHpA showed little or no concentration increase with repeated exposure. Elimination half-lives of PFHxA, PFHpA and 5:3 Acid in humans were estimated from a study of professional ski wax technicians who were occupationally exposed to aerosolized and volatilized components of fluorinated glide wax. The resulting human elimination half-life values of PFHxA, PFHpA and 5:3 Acid were 32, 70 and 43 d, respectively. Based on a one compartment toxicokinetic model, current environmental air concentrations of 6:2 FTOH are estimated to result in plasma concentrations of PFHxA, PFHpA and 5:3 Acid that are less than or equal to typical LOQ values, in agreement with extant biomonitoring results.